Educational Strategies of Islamic Boarding Schools in Internalizing Islamic Values within Multicultural Societies - Ma’mun Hanif; Diah Anisa Lestari; Khulatul Jannah; Putri Kurnia Sari; Najmi Arif Triyadi; Muhamad Rizki Zidan (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
This study examines how Islamic boarding schools (pesantren) internalize Islamic values within a multicultural social environment in Bali, Indonesia, where Muslims constitute a minority group. The research addresses the limited empirical understanding of pesantren-based value education in minority-Muslim contexts characterized by strong cultural and religious diversity. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews with pesantren leaders, teachers, and students, as well as document analysis of curricula and institutional educational policies. The findings indicate that Islamic values are primarily internalized through daily educational practices, habituation, and educators’ role modeling rather than through formal instruction alone. Pesantren employ adaptive educational strategies that emphasize universal ethical values such as tolerance, respect, and peaceful coexistence, enabling students to engage constructively within Bali’s multicultural society. These strategies contribute to observable changes in students’ social attitudes and behaviors, reflecting the development of inclusive and context-sensitive religious understanding. Although this study is limited by its focus on a specific sociocultural setting, the findings provide important insights into the role of pesantren as agents of character formation and religious moderation in plural societies.